LIKA: lightweight identity based key agreement protocol for secure data transmission in advanced metering infrastructure of smart grid - Hasan, Md Mehedi; Mohd Ariffin, Noor Afiza; Mohd Sani, Nor Fazlida (MDPI AG, 2022)
Integration of information communication technology via the Internet of Things devices and sensors can enable an efficient power service for utility providers to consumers in advanced metering infrastructure. Authentication and cryptographic mechanisms protect identity, data security and privacy from unauthorised interception for smart meters to servers. In the last couple of years, many key agreement protocols have been prescribed and deployed to fix those issues. Unfortunately, the deployed protocols did not work inside the same protocols, specifically parameter detection and recognition for session key generation, as they entail high computation time and communication bits overheads. Furthermore, the absence of forward secrecy and user anonymity affects the authentication. Therefore, we have proposed a lightweight identity-based key agreement (LIKA) utilising the Diffie–Hellman cryptography with a trusted authority. It seeks to cover both the security and performance criteria with equal weight. The protocol is evaluated by the Canetti and Krawczyk adversarial model, Avispa and cryptographic analysis released the session keys that were not considered as an adversary during mutual authentication. Moreover, as compared to related work, the proposed protocol took the least amount of time (5.319 ms and 1056 bits) for the entire process of session key generation. Furthermore, comparative analysis has shown that the LIKA adequately encompasses computation, communication, and security assessments. Consequently, it is more convenient for practical implementation for a smart grid.